Application of dry electrodes in supercapacitors and lithium-ion batteries - Guolei ZHANG; Keliang ZHANG; Yabin AN; Chen LI; Guanwei LIU; Xianzhong SUN; Changzhou YUAN; Kai WANG; Xiong ZHANG; Yanwei MA (工程科学学报)
With the increasing demand for electrochemical energy storage, the lithium-ion battery industry faces new challenges, such as improving production efficiency, reducing energy consumption, and enhancing battery performance, especially for next-generation batteries. Among these challenges, electrode manufacturing is crucial as it significantly influences the energy density, manufacturing costs, and yield of lithium-ion batteries. Dry electrode technology is a new type of electrode manufacturing process that shows great potential in supercapacitors and lithium-ion batteries. It offers significant advantages such as high surface density, low internal resistance, and long cycle performance, all without the need for adding any solvents. The unique benefits of this technology have sparked considerable attention from both academia and manufacturing industries. This review compares traditional wet-process electrode technology with emerging dry electrode technology. It begins with outlining the preparation methods, characteristics, and distinct features of dry electrode processes and then discusses in detail the research progress and applications of the technology in supercapacitors and lithium-ion batteries, including advancements in electrode loading and electrochemical performance. Key dry processing techniques include dry spray deposition, powder compression, and polymer binder fiberization, each with its unique technical features and all following a consistent process of dry blending, dry coating (dry deposition), and electrode pressing. Compared to traditional supercapacitor electrode technology, dry process technology offers four major advantages: improved battery performance, reduced production costs, environmental conservation, and expanded application potential. The article extensively discusses the research progress in dry electrode research for supercapacitors and lithium batteries, emphasizing improvements in electrode loading and electrochemical performance. It covers the preparation of dry electrodes using various materials like carbon, lithium cobalt oxide, ternary lithium materials, lithium iron phosphate, and solid electrolytes. Optimizing preparation processes and structural designs further enhances dry electrode performance. Without solvents, dry process technology is suitable for liquid-sensitive systems, unlike traditional liquid electrolytes, which pose safety issues such as flammability and explosiveness. Solid electrolytes, especially those containing sulfur, are often sensitive to polar solvents and prone to decomposition, shortening their cycling life. The use of dry electrolytes offers a promising solution to this problem, promoting the preparation of dry electrolytes and the development of all-solid-state batteries. Additionally, dry processing techniques can be applied to prelithiation. Finally, the challenges and issues in the current use of dry electrodes in supercapacitors and lithium-ion batteries are summarized, along with proposed future directions. As a promising electrode manufacturing technology, dry technology holds the potential to replace the wet process technology widely used in state-of-the-art commercial lithium-ion batteries. However, numerous challenges must be overcome before this technology can be commercialized. Before replacing wet process technology, significant improvements and developments are needed in dry electrode technology, especially in determining electrode parameters and selecting suitable binders for different dry process technologies. The development of binders for dry process technology is ongoing, and beyond polyvinylidene fluoride and polytetrafluoroethylene, modified binders meeting various process requirements are crucial research topics.